Evaluation of Certain Inflammatory Markers in Transfusion Dependent β- Thalassemic Patients (Tikrit Journal of Pharmaceutical Sciences, 2025)
To determine the serum concentration of certain inflammatory markersincluding TNF-α and hs-CRPβ-thalassemic patients on different types oftreatmentand to investigate the possible correlation between theseinflammatory markers and iron overload referred to by serum ferritinconcentration, moreoverto assesswhether inflammation in β-thalassemiacould be controlled by deferasirox or deferoxamine as compared totransfusion dependent patients without iron chelator. Ninety transfusiondependent β-thalassemic children with age range 13–75 months wereincluded in this study, and 30 age and sex matched healthy subjectsserved as control,thepatients were divided into three groups according tothe type of the treatment,each group included 30 patients Group1comprised β-thalassemic patients without iron chelator, Group2comprisedβ-thalassemic patients on deferasirox iron chelator whileGroup3 comprisedβ-thalassemic patients on deferoxamine iron chelator.Serum ferritin, hs-CRP, and TNF-α was measured for all participants byELISA method. Compared with the control, the serum level of ferritinand hs-CRP were significantly elevated in all patients groups while theserum level of TNF-α were only significantly elevated in Group1 andGroup3. Further analysis of the results revealed positive correlationbetween serum ferritin withTNF-α and with hs-CRP.A comparisonamong the patients groups show that patients on deferasirox (Group2) hadsignificantly low level of TNF-α as compared to Group1 and Group3. Onthe other hand serum ferritin and hs-CRP concentration in Group3 weresignificantly higher than the other two groups, furthermore when Group3patients are subdivided according to their compliance on deferoxaminetheresult show that the serum level of ferritin, hs-CRP and TNF-α aresignificantly higher in poor compliance subgroup as compared to goodcompliancepatients and when good compliance subgroup are comparedwith Group2 no significant deference in the measured parameter wasfound. Chronic inflammatory state is present in these patientswithincreased levels of inflammatory markers such as TNF-α andCRP.The observed correlations of ferritin with inflammatory markers implythat iron overload may play a key role in release of these markers.Chelation Therapy with deferasirox can attenuate inflammation andreduces inflammatory markers level while deferoxamine appear to be lesseffective as most patients suffer from poor compliance on this type ofiron chelator